2008
DOI: 10.1051/0004-6361:20078675
|View full text |Cite
|
Sign up to set email alerts
|

Structural signatures of medium-range order in annealed laboratory silicates

Abstract: Context. Silicate dust grains exist in a wide range of astronomical environments and understanding the effect of these on grain structure is of great interest, particularly the effect of thermal annealing on amorphous silicates as a possible route to the formation of crystalline grains. Although laboratory simulations have largely focussed on IR-spectroscopic measurements, since these relate directly to observational data, laboratory synchrotron techniques such as X-ray absorption spectroscopy (XAS) and X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 96 publications
(100 reference statements)
2
22
1
Order By: Relevance
“…The observed spectrum is consistent with those reported by Wu et al 9,10 and Thompson. 11 In the crystal phase, four characteristic peaks, denoted as A to D, 11 and a shoulder at 1308 eV are observed. The spectra of the amorphous phase are smeared, in particular, above 1320 eV.…”
Section: A Xanes Spectra Of Forsterite In Crystal and Amorphous Phasesmentioning
confidence: 99%
“…The observed spectrum is consistent with those reported by Wu et al 9,10 and Thompson. 11 In the crystal phase, four characteristic peaks, denoted as A to D, 11 and a shoulder at 1308 eV are observed. The spectra of the amorphous phase are smeared, in particular, above 1320 eV.…”
Section: A Xanes Spectra Of Forsterite In Crystal and Amorphous Phasesmentioning
confidence: 99%
“…Owing to the difference in structure of the samples used, we have not considered the size effect in this work. Prior to the Infrared Space Observatory, it was reported that silicates formed as disordered or amorphous grains in the outflows of O-rich stars at various stages of their evolution [32,33] and very likely that they are a precursor to the crystalline silicates [34]. Therefore, it is of interest to investigate the catalytic conversion of C 2 H 2 on the surface of amorphous enstatite grains.…”
Section: Resultsmentioning
confidence: 99%
“…The annealing time at peak temperature for each sample was ∼17.5 ± 1 h. This method of sample preparation while obviously not mimicking the formation conditions of cosmic grains, has been found by us to consistently produce an amorphous silicate with reproducible properties providing good parity between different investigations. As such, the sample prepared for the present work is equivelent to the Product I silicate refered to in Thompson (2008), Thompson et al (2007) and the MgSiO 3 silicates in earlier works (Thompson et al 2002(Thompson et al , 2003Thompson & Tang 2001).…”
Section: Sample Manufacturementioning
confidence: 99%
“…Previously (Thompson 2008), the presence and extent of medium-range structure in three amorphous Mg-silicates annealed over coarse temperature intervals was investigated using X-ray absorption near edge structure (XANES) spectroscopy and by X-ray scattering. The XANES data showed the growth of medium-range structure from 5 to 10 Å; while certain X-ray scattering features at low values of the X-ray scattering vector were identified with correlations between medium-range structures with differing tetrahedral connectivity.…”
Section: Medium-range Structurementioning
confidence: 99%
See 1 more Smart Citation